Remarks at Opening Press Conference, IMF/World Bank Spring Meetings, Washington, D.C., April 18, 2013 - Kim, Jim Yong (2016)
Jim Yong Kim, President of the World Bank Group, discusses the issues to end extreme poverty in the World, promoting shared prosperity, and taking bold action on climate change. He speaks about accelerating the high growth rate in the developing world, and to translate this into poverty reduction and job creation. It must be inclusive to curb inequality. He insists that we must avert or mitigate potential shocks such as climate disasters or new crises in food, fuel, and finances. Climate change is not just an environmental challenge, but also a fundamental threat to economic development. He also believes that the combined efforts of the United Nations and the World Bank Group on the political and security fronts can make a major difference in moving fragile states out of fragility. He fields questions about a BRICS development bank, Chinese growth and inequality, the World Bank Group’s financial commitments on climate change, Peruvian poverty, loan conditionality, monetary policies of emerging countries, China’s urbanization, Caribbean economies, the Arab Spring countries, and Mexican economic reform.